MANAJEMEN DAN LINGKUNGAN PENDIDIKAN ISLAM - Nurasa Nurasa (IAIN Batusangkar, 2016)
Management and Environmental Islamic Education. Proceed from the assumption that life is education and education is life in the sense of education as a matter of life and living, the discourse about education is one topic that is always interesting. There are at least two reasons can be identified so as to keep up to date education to be studied. First, the need for education is crucial because it is intrinsically linked directly to the realm of life and human life. To discuss education means talking human needs. Second, education is also a strategic vehicle for efforts to improve the quality of human life, which is characterized by increased levels of well-being, poverty and decreasing the volume of the opening of the various alternative options and opportunities to actualize themselves in the future. In realizing that there are three factors that need attention, namely parents factors, school factors, and environmental factors society.Kata Kunci : Manajemen, lingkungan, pendidikan Islam